Aspiration Due to Difficulty in Swallowing. Issue 250 (December 1971) - Matsaniotis, N.; Karpouzas, J.; Tzortzatou-Vallianou, M.; Tsagournis, E.
Abstract : The swallowing mechanism after a propyliodone (`dionosil') swallow was studied in 44 infants, aged 6 days to 6 months, who were admitted during a 6-month period to the Paediatric Clinic of Athens University because of choking spells during feedings or persistent vomiting. Twenty-three infants showed aspiration of the opaque material into the tracheobronchial tree. The incidence of aspiration was very high. It declined, however, with increasing age, indicating that it is a benign condition which might be related to neuromuscular immaturity in early life.